Characterization of the key odorants of crucian carp soup and flavour improvement by modulated temperature mode in electrical stewpot. (19th September 2021) - Zhang, Man; Chen, Mengfei; Xing, Suhui
Abstract: Fish soup was usually prepared in electrical stewpot instead of traditional purple clay stewpot due to its convenience nowadays; however, fish soup prepared in electrical stewpot at a high temperature for a long time resulted in flavour deterioration. The flavour profile of crucian carp soup prepared in high temperature modes (traditional purple clay stewpot (TS) and commercial ceramic electrical stewpot (CS)) and low temperature modes (electrical stewpot with low temperature modulation modes (TM1 ‐TM6 )) was studied by sensory evaluation, gas chromatography‐mass spectrometry (GC‐MS) and GC‐MS/olfactometry (GC‐MS/O). Results indicated that crucian carp soup prepared in TM2 (heating rate of 2.44°C/min, constant temperature time of 20 min, low temperature of 90°C, low temperature time of 60 min) had favourable sensory characteristic with stronger cooked fish and fatty aroma and lower off‐flavour. Twenty‐six odorants in crucian carp soup were identified by GC‐MS/O. Of these, 8 odour‐active compounds presented odour activity values (OAVs) greater than 1, with several aldehydes and 1‐octen‐3‐ol contributing as important odorants of crucian carp soup. TM2 samples exhibited higher OAVs in these 8 odorants compared with CS and other TM samples. The umami‐taste amino acids in TM2 accounted for a higher proportion compared to TS and CS samples. The correlation analysis between sensory characteristics and odorants through partial least squares regression (PLSR) indicated that octanal, decanal and 1‐octen‐3‐ol were significantly and positively associated with cooked fish note. Heptanal, octanal, decanal and (E, E)‐2, 4‐decadienal significantly and positively linked with fatty note. (E, E)‐2, 4‐Decadienal showed a significant and negative correlation with fishy odour. Abstract : Characterization of the key odorants of crucian carp soup by sensory evaluation, gas chromatography‐mass spectrometry/olfactometry, odour activity values and partial least squares regression and flavour improvement in stewpot.